The Relationship Between the Implementation of the Implementation of the Demonstration Method and Student Learning Motivation in Fiqh Subject at Said Yusuf Islamic Junior High School Depok - Eva Siti Faridah; Huliyatul Atqiya (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
Learning motivation refers to the internal drive within students that encourages them to acquire knowledge to achieve the success they aspire to. The lack of learning motivation in students becomes a challenge because the teacher’s teaching strategies are less innovative, particularly in applying teaching methods. The purpose of this research is to determine the relationship between the Demonstration Method and learning motivation at SMP Islam Said Yusuf Depok. The research variables include the Demonstration Method (X) and Learning Motivation (Y). The population in this study consisted of all students at Sa'id Yusuf Islamic Middle School, totaling 131 individuals. The sampling technique used was purposive sampling, so the sample taken specifically for class VIII students amounted to 50 people. Data was collected through observation, interviews, questionnaires, and documents. Data analysis was performed using SPSS statistics, including data description, validity test, reliability test, normality test, linearity test, and correlation test with product-moment Pearson correlation, significance test, and coefficient of determination. The data description for the Demonstration Method shows an average score of 125.62, a median of 127.50, a mode of 130, a standard deviation of 8.647, and a variance of 74.771, with the highest score being 147 and the lowest being 106. The data description for learning motivation shows an average score of 116.96, a median of 118.00, a mode of 102, a standard deviation of 8.647, and a variance of 329.546, with the highest score being 148 and the lowest being 78. The hypothesis test results, which examine the relationship between the Demonstration Method (variable X) and learning motivation (variable Y), show a correlation coefficient of r = 0.393 > r table 0.279. Therefore, Ha is accepted, and Ho is rejected, indicating a positive relationship between the demonstration method and learning motivation in Fiqih subjects at SMP Islam Said Yusuf Depok. The correlation between these variables is statistically significant, as demonstrated by the t-test value of 2.960 > t table 2.021. The coefficient of determination is 0.154, meaning the contribution of the Demonstration Method to learning motivation is 15.4%, with the remaining influence coming from other factors.